GCN5 Is a Master Regulator of Gene Expression in the Malaria Parasite Plasmodium falciparum - Amuza Byaruhanga Lucky; Ahmad Rushdi Shakri; Xiaoying Liang; Hui Min; Xiao-Lian Li; Swamy Rakesh Adapa; Rays H. Y. Jiang; Liwang Cui; Chengqi Wang; Jun Miao (Cells, 2025)
GCN5-containing SAGA complex is evolutionarily conserved across yeast, plants, and humans and acts as a general transcription coactivator in the genome-wide regulation of genes. In Plasmodium falciparum, PfGCN5 forms a divergent complex, and the mis-localization of this complex by deleting the PfGCN5 bromodomain (ΔBrd) causes a plethora of growth defects. To directly test the PfGCN5 function, we performed conditional knockdown (KD) of PfGCN5. Whereas PfGCN5 KD phenotypically recapitulated the ΔBrd growth defects, it caused fewer transcriptional alterations compared to ΔBrd. To decipher the mechanism by which PfGCN5 regulates gene expression, we applied a new chromatin landscape analysis tool, CUT&Tag-seq, to map the chromatin localization of PfGCN5 and its deposited histone mark H3K9ac. Compared to ChIP-seq, CUT&Tag-seq identified substantially more H3K9ac peaks in the promoters of its target genes, with the peak intensity positively correlated with the levels of gene expression. CUT&Tag-seq analysis was remarkably more sensitive in mapping chromatin positions of PfGCN5, which colocalized with H3K9ac. The genes enriched with PfGCN5/H3K9ac signals at their promoters are involved in broad biological processes. Notably, PfGCN5′s positions overlapped with sequence motifs recognized by multiple apetela2 (AP2)-domain-containing transcription factors (AP2 TFs), suggesting that they recruited PfGCN5 to these promoters. Additionally, PfGCN5 was also colocalized with AP2-LT, further validating that AP2-LT is an integral component of the PfGCN5 complex. Collectively, these findings establish PfGCN5 as a master gene regulator in controlling general and parasite-specific cellular processes in this low-branching parasitic protist.